Whole genome sequencing of melanomas in adolescent and young adults reveals distinct mutation landscapes and the potential role of germline variants in disease susceptibility. Issue 5 (21st November 2018) - Wilmott, James S.; Johansson, Peter A.; Newell, Felicity; Waddell, Nicola; Ferguson, Peter; Quek, Camelia; Patch, Ann‐Marie; Nones, Katia; Shang, Ping; Pritchard, Antonia L.; Kazakoff, Stephen; Holmes, Oliver; et al.
Abstract : Cutaneous melanoma accounts for at least >10% of all cancers in adolescents and young adults (AYA, 15–30 years of age) in Western countries. To date, little is known about the correlations between germline variants and somatic mutations and mutation signatures in AYA melanoma patients that might explain why they have developed a cancer predominantly affecting those over 65 years of age. We performed genomic analysis of 50 AYA melanoma patients (onset 10–30 years, median 20); 25 underwent whole genome sequencing (WGS) of both tumor and germline DNA, exome data were retrieved from 12 TCGA AYA cases, and targeted DNA sequencing was conducted on 13 cases. The AYA cases were compared with WGS data from 121 adult cutaneous melanomas. Similar to mature adult cutaneous melanomas, AYA melanomas showed a high mutation burden and mutation signatures of ultraviolet radiation (UVR) damage. The frequencies of somatic mutations in BRAF (96%) and PTEN (36%) in the AYA WGS cohort were double the rates observed in adult melanomas ( Q < 6.0 × 10 −6 and 0.028, respectively). Furthermore, AYA melanomas contained a higher proportion of non‐UVR‐related mutation signatures than mature adult melanomas as a proportion of total mutation burden ( p = 2.0 × 10 −4 ). Interestingly, these non‐UVR mutation signatures relate to APOBEC or mismatch repair pathways, and germline variants in related genes were observed in some of these cases. We conclude that AYA melanomas harbor some of the same molecular aberrations and mutagenic insults occurring in older adults, but in different proportions. Germline variants that may have conferred disease susceptibility correlated with somatic mutation signatures in a subset of AYA melanomas. Abstract : What's new? Melanoma is a leading cause of cancer death in adolescents and young adults (AYA) in Western countries. Little is known, however, about the contribution of genetic factors to AYA melanoma risk. Here, genomic analyses show that AYA melanomas, similar to adult cutaneous melanomas, have a high mutation burden, with mutations indicative of ultraviolet radiation (UVR) damage. AYA tumors further exhibited increased somatic mutation rates in key melanoma driver genes and had a higher proportion of non‐UVR mutation signatures relative to adult melanomas. Germline variants identified in an AYA patient subset suggests a role for dysfunctional DNA maintenance in AYA melanoma susceptibility.